The Origin of the Cube ({001}<100>) Texture in Non-oriented Electrical Steel Sheets. Issue 1 (March 2021) - He, Youliang; Mehdi, M; Hilinski, E J; Kestens, L A I; Edrisy, A
Abstract: Although cube ({001}<100>) is a preferred final texture in non-oriented electrical steel (NOES) sheets, this texture is rarely produced in commercial NOES products. The major texture of fully processed NOES is usually the unfavorable <111>//ND (normal direction) fibre, which originates from the deformed <111>//ND texture. To reduce/eliminate the <111>//ND texture and promote the cube texture, one method is to change the initial texture before cold rolling. In this research, two electrical steels containing 0.88 wt% and 2.8 wt% Si are cold rolled with the initial textures rotated by 60° around the ND before cold rolling. This rotation leads to the rotated Goss ({110}<110>) texture in the deformed microstructure. Within the shear bands of the rotated Goss grains, crystallites with cube orientation are formed. Regions of these crystallites may have lower stored energy than their neighboring areas. During annealing, these crystallites preferentially nucleate and grow, and form a strong cube texture in the final steel sheets.